How to Solve the Time Dilemma? The Influence of Team Temporal Leadership on Team Innovation Performance - Liu, Zhengqiao; Liu, Xiliang; Zhang, Xianchun (Frontiers in Psychology, 2021)
Time pressure (TP) is the most common kind of pressure faced by R&D teams. How to improve team innovation performance (TIP) when time resources are insufficient has been a concern of practitioners and scholars. The purpose of this paper is to put forward some suggestions to solve that time dilemma. We conduct a survey based on a sample of 163 teams. In the first-stage survey (time 1), we measure the team temporal leadership (TTL) and TP. In the second-stage survey (time 2), we measure team learning behavior (TLB). TIP was measured in the third-wave survey (time 3). The results are as following: (i) TTL has a significant positive impact on the TLB and TIP; (ii) TLB plays a mediating role in the relationship between TTL and TIP; (iii) TP can positively moderate the relationship between TTL and TLB, that is, the promoting effect of TTL on TLB is more pronounced under the higher level of TP. These findings reveal the influence mechanism of TTL on TIP from the perspective of TLB and TP.